Strategi Pengembangan Pariwisata Berbasis Potensi: Analisis SWOT Desa Wisata di Sekitar Candi Borobudur - Yubdina, Salma; Rini, Dewi Kartika; Maharani, Ni Made Shinta Dwi; Khairiyah, Nurul; Prasetyo, Andre Dwi; Azzahara, Aisyia (JURNAL NASIONAL PARIWISATA, 2024)
The potential of the tourism sector plays an important role in supporting local and global economic growth. The trend of developing rural tourism or tourist villages is interesting to study, considering that each region in Indonesia has its own natural and cultural wealth. One of them is the tourist village in the Borobudur area. This study aims to explore the tourism potential in these villages using a SWOT analysis, focusing on their natural and cultural heritage represented by Borobudur Temple. The Village Economic Center, which was built on the initiative of the government, aims to increase economic opportunities by utilizing local wisdom in offering accommodation and cultural experiences, thereby extending the length of stay of tourists. This study uses a qualitative approach, including interviews and literature studies, to understand the perspectives of stakeholders in Karangrejo Tourism Village and its surroundings. The findings show that although these villages have the strength of beautiful natural landscapes and rich cultural assets, issues such as environmental preservation and community involvement remain crucial for sustainable tourism development. This study contributes to the discussion on village tourism development strategies based on the results of a SWOT analysis with an emphasis on community involvement and sustainable practices to encourage local economic growth. Future research can explore broader stakeholder perspectives using analytical frameworks other than SWOT for a more comprehensive planning strategy.